Interplay Between Silicon and Iron Signaling Pathways to Regulate Silicon Transporter Lsi1 Expression in Rice - Chaiwong, Nanthana; Bouain, Nadia; Prom-u-thai, Chanakan; Rouached, Hatem (Frontiers in Plant Science, 2020)
Silicon (Si) is not an essential element, but it is a beneficial element for growth and development of many plant species. Nevertheless, how plants regulate the initial uptake of silicon (Si) remains poorly understood. The current model for the regulation of Si uptake is reductionist as it takes into account only Si availability and does not consider the availability of essential micro-elements such as iron (Fe). Therefore, the present study investigates the regulation of the Si transporter Lsi1, in three rice varieties grown under different Si and Fe regimes. The Lsi1 transcript was compared to intracellular concentrations of Si and Fe in roots. The amount of Lsi1 transcript was mainly altered in response to Si-related treatments. Split-root experiments showed that the expression of Lsi1 is locally and systemically regulated in response to Si signals. Interestingly, the accumulation of Lsi1 transcripts appeared to be dependent on Fe availability in root growth environment. Results suggest that the expression of Lsi1 depends on Si and Fe signals crosstalk. This finding is the first step toward a better understanding of the co-regulation of Si homeostasis with other essential nutrients in plants. This response was conserved in the three rice cultivars tested. Finally, our data clearly show that a better understanding of Si/Fe signalling is needed to define the fundamental principles supporting plant health and nutrition.